MONITORING SUHU AIR PADA KOLAM IKAN KOI BERBASIS BLYNK - Ozi, Zulhan Ozi Firmanu; Lalu A. Syamsul Irfan Akbar (Depertment of Electrical Engineering University of Mataram, 2023)
Koi fish is a type of fish that is in great demand by all levels of society, with various body patterns and colors. Koi fish have high economic value and promising business potential, so they are widely cultivated. Koi fish need more attention in cultivation. One growth factor that can be seen is remote monitoring of pool temperature. The ideal temperature for koi fish is between 24℃ – 30℃. So we need a tool that is used to facilitate monitoring of temperature in koi fish ponds remotely. By using the DS18B20 temperature sensor, ESP32 microcontroller and using one of the IoT platforms, namely Blynk. IoT is a concept utilization that aims to expand the benefits of continuously connected internet connectivity. The sensor will send temperature measurement results to the ESP32 microcontroller, ESP32 which is connected to an Internet-connected Access Point will send temperature measurement results to the cloud and can be seen in the Blynk software. Based on the test, it can be concluded that the whole process went well according to the design and initial purpose of making a Blynk-based koi pond water temperature monitoring system.